An Application of Axiomatic Design and Constraints Relation Matrix in Engineering Design Process - พรมสุ้ย คึกฤทธิ์ (Srinakharinwirot University Engineering Journal, 2018)
Redesign often occurs during the process of the engineering design to meet specifications of customer requirements in term of functional requirements and usage limitations, since the requirements cannot be completely analyzed at the beginning and during the design process. To reduce this problem, this research proposes the application of using axiomatic design theory to analyze the function structure and physical design by applying the Constraint Relation Matrix (CRM), that was developed to consider the relationship between the design solution and design constraints at every step of the decision making for reducing the possible alternatives of design solution. The design constraints are classified into two types: operation constraints, which are considered in module level, and technique constraints, which are considered in sub module until part level. By understanding the relationship of constraints at every level, all constraints will be considered together with all component parts related during the design process for confirming, that all constraints will be considered and the designer will not face to the problem of the redesign.